2016
DOI: 10.1111/cobi.12727
|View full text |Cite
|
Sign up to set email alerts
|

The role of digital data entry in participatory environmental monitoring

Abstract: Many argue that monitoring conducted exclusively by scientists is insufficient to address ongoing environmental challenges. One solution entails the use of mobile digital devices in participatory monitoring (PM) programs. But how digital data entry affects programs with varying levels of stakeholder participation, from nonscientists collecting field data to nonscientists administering every step of a monitoring program, remains unclear. We reviewed the successes, in terms of management interventions and sustai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 47 publications
4
28
0
Order By: Relevance
“…We deem our scenario assumptions valid within the 2025 time frame, while in the longer term other emerging processes could significantly affect socioeconomic and environmental trajectories, in particular natural gas and oil extraction, rural-to-urban migration, introduction of PES schemes, IT development, climate change, and capacity building. Our outputs should be interpreted jointly as an expression of a large, though limited, number of stakeholders, at the time (2014) and at the scale (macro-regions) of the workshops, and should be used along with, and not in replacement of, other analytical approaches, particularly those that harness representation at local scales (e.g., Enfors et al 2008, Tschakert and Dietrich 2010, Brammer et al 2016). …”
Section: Integrated Socioeconomic and Environmental Scenarios In Tanzmentioning
confidence: 99%
“…We deem our scenario assumptions valid within the 2025 time frame, while in the longer term other emerging processes could significantly affect socioeconomic and environmental trajectories, in particular natural gas and oil extraction, rural-to-urban migration, introduction of PES schemes, IT development, climate change, and capacity building. Our outputs should be interpreted jointly as an expression of a large, though limited, number of stakeholders, at the time (2014) and at the scale (macro-regions) of the workshops, and should be used along with, and not in replacement of, other analytical approaches, particularly those that harness representation at local scales (e.g., Enfors et al 2008, Tschakert and Dietrich 2010, Brammer et al 2016). …”
Section: Integrated Socioeconomic and Environmental Scenarios In Tanzmentioning
confidence: 99%
“…However, there is also concern that dependence on networked electronic devices carries the risks of frequent equipment failures in remote settings and of improper use [5, 21]. A recent review found digital data entry can contribute to the success of participatory monitoring when combined with stakeholder participation, but it may have detrimental effects on the sustainability of the monitoring if it is not effectively implemented [43]. Thus, the increased ease of reporting gained from the use of those devices should be considered against the risks.…”
Section: Discussionmentioning
confidence: 99%
“…Advantages of these tools over pen and paper include fewer errors, improved accuracy, shorter processing time, and more useful data for analysis and decision making. Digital tools may also help bridge the gap between participatory and scientific monitoring when the technical aspects of sampling and data analyses are automated (Laake et al 2013;Pratihast et al 2014;Bellfield et al 2015;Brammer et al 2016). There are disadvantages too, such as the cost of training and technical support, and thus dependence on outside resources, and alienation of groups who may be less familiar with digital tools (Brammer et al 2016).…”
Section: Selecting Monitoring Methodsmentioning
confidence: 99%
“…; Brammer et al. ). There are disadvantages too, such as the cost of training and technical support, and thus dependence on outside resources, and alienation of groups who may be less familiar with digital tools (Brammer et al.…”
Section: Key Messagesmentioning
confidence: 97%
See 1 more Smart Citation